Ecotoxicological insight of phytochemicals, toxicological informatics, and heavy metal concentration in Tridax procumbens L. in geothermal areas - N.B. Maulydia; R. Idroes; K. Khairan; T.E. Tallei; F. Mohd Fauzi (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Tridax procumbens L. is a plant that grows abundantly in the Ie-Seu'um geothermal area in Aceh Province, Indonesia. The objective of this study is to determine metabolite compounds from Tridax procumbens plants in a geothermal area using qualitative and quantitative analyses. In addition, the contents of six heavy metals in plants and their toxicology were assessed using an in silico approach.METHODS: The ethanolic extract of Tridax procumbens was analyzed qualitatively using reagents to determine the contents of secondary metabolites such as flavonoids, alkaloids, tannins, steroids, triterpenoids, and saponins. In addition, quantitative analysis was conducted using gas chromatography–mass spectroscopy to obtain the chromatograms and mass spectra of the metabolite compounds of the ethanolic extract of Tridax procumbens, which were used in computational toxicology analysis using a simplified molecular input system in a predictor server. Atomic absorption spectrometry was conducted to confirm the contents of six heavy metals harmful to medicinal plants.FINDINGS: The results showed that Tridax procumbens from the Ie-Seu'um geothermal area, Aceh, has secondary metabolites such as flavonoids, saponins, steroids, and tannins, with phytol from diterpenoid group having the highest content (32.72 percent). Toxicological analysis showed that the compounds in the ethanolic extract of Tridax procumbens were nontoxic or inactive in five toxicity parameters. The other results of the heavy metal analysis showed the dominance of chromium among the other six metals tested (copper, not detected; cadmium, 0.91 ± 0.03 milligram per kilogram; zinc, 3.50 ± 0.03 milligram per kilogram; iron, 4.65 ± 0.02 milligram per kilogram; lead, 6.42 ± 0.05 milligram per kilogram; and chromium, 13.81 ± 0.07 milligram per kilogram.CONCLUSION: This study highlights the unique secondary metabolite composition of Tridax procumbens under such extreme conditions and underscores the potential implications of heavy metal accumulation in plants in geothermal areas.